British crime survey, 2000: X4L SDiT teaching dataset - Corti, Louise (UK Data Service, 2004)
The British Crime Survey, 2000: X4L SDiT Teaching Dataset (BCS) is a stripped-down version of the full BCS 2000 study held as study number 4463 at the UK Data Archive. The dataset is drawn from the 'non-victim' BCS data and contains just 33 variables, some broadbanded to protect respondent confidentiality. The dataset forms part of a wider SDiT project, which is accessible via the X4L - SDiT (Survey Data in Teaching) project web site. This project aimed to improve data literacy for students of survey methods and statistics.